Quality analysis of developed multigrain flour mixes - Sangma, Nikita RST; Das, Pranati; Baruah, Luna Dutta; Dutta, Manisha (Journal of Postharvest Technology, 2021)
The present research work on nutrient evaluation of multigrain flour mix was carried to standardize a simple, nutritional blends by utilizing wheat,  foxtail millet, maize, Bengal gram and pumpkin seed with the objectives to develop and study the nutritional quality and sensory evaluation of a  multigrain flour mix. Five blends were made Mix 1, Mix 2, Mix 3, Mix 4 and Mix 5 whole wheat, foxtail millet, maize, Bengal gram and pumpkin  seed in the ratios (90:10), (80:10:10), (70:10:10:10) and (60:10:10:10:10), respectively. The formulated multigrain mixes were subjected to  nutrient, physical, functional and sensory evaluation. The mixes were found to be more nutrient dense than the control. The colour and texture  analyses of the mixes showed better results than the control. The Mix 3 contained the highest water absorption capacity and oil absorption  capacity was highest in Mix 5. The acceptability trial was done on multigrain mix based chappatis and it was found that the Mix 5 was found  acceptable (8.89 ± 0.60). Therefore, the formulations can be utilized for popularization, commercialization and development of such functional  foods that would be beneficial to improve the general health status of populations..
Keywords: Functional analysis; multigrain mix; nutrient analysis; physical analysis; sensory evaluation